Penerapan Model Pembelajaran Kooperatif Student Team Achievement Division dalam Meningkatkan Hasil Belajar Kewarganegaraan Siswa Kelas V SDN Nanggeleng I Kota Sukabumi - Julaeha, Ooy (FKIP Universitas Muhammadiyah Sukabumi, 2018)
Application of the Student Team Achievement Division Cooperative learning model inimproving the learning outcomes of citizenship education. Research with a classroom actionresearch approach was carried out collaboratively and two cycles. The main objective of thisstudy was to determine the improvement in learning outcomes of fifth grade students ofNanggeleng I Elementary School in subdistrict of Citamiang, Sukabumi City on CitizenshipEducation subjects by applying the cooperative learning model of the Student TeamAchievement Division. The research was conducted at Nanggeleng I Elementary School, insubdistrict of Citamiang, Sukabumi City, which was held in the first semester of September2015. The subjects of this research were 37 students of the fifth grade of Nanggeleng IElementary School, Citamiang subdistrict. The results showed that the average value oflearning outcomes in the first cycle scored 68.10 with a percentage of 70.27%, while in thesecond cycle obtained a value of 70.27 with a percentage of 94.59%, meaning that there was anincrease / improvement in student learning outcomes. Likewise the results of studentobservations showed an increase in the speed, participation, cooperation, and accuracy ofstudents by obtaining scores in the first cycle of 69.45%, while in the second cycle they scored69.45%. This study concluded that the application of the cooperative learning model of the Student Team Achievement Division could improve the learning outcomes of citizenship subjects of the V grade Nanggeleng I Elementary School in Citamiang District, Sukabumi City. Inaddition, the application of this learning model can improve the speed, participation,cooperation, and accuracy of students in the learning process.